190k views
5 votes
PLEASE HELP I've been struggling on this one :(

PLEASE HELP I've been struggling on this one :(-example-1
User Richvdh
by
4.6k points

2 Answers

0 votes

Answer: The answer is (x+2)(x-4)(x-4)
Or as a short form you can write it as

(x+2) (x-4)^(2)

Explanation:

Answer is very lengthy but I am 100% sure that's the correct answer

User The Go Company
by
5.4k points
5 votes

Answer:

(x³ - 6x² + 32) = (x - 4)²(x + 2)

Explanation:

(x³ - 6x² + 32)/(x - 4) =

x² - 2x - 8

----------------------------------

x - 4 | x³ - 6x² + 0x + 32

x³ - 4x²

----------

-2x² + 0x

-2x² + 8x

----------------

-8x + 32

-8x + 32

-------------

0

(x³ - 6x² + 32) = (x - 4)(x² - 2x - 8) = (x - 4)(x - 4)(x + 2) =

= (x - 4)²(x + 2)

User Wallace
by
4.6k points